2019
DOI: 10.1002/ange.201905729
|View full text |Cite
|
Sign up to set email alerts
|

Fluorographdiyne: A Metal‐Free Catalyst for Applications in Water Reduction and Oxidation

Abstract: Ah ighly efficient bifunctional metal-free catalyst was prepared by growth of three-dimensional porous fluorographdiyne networks on carbon cloth (p-FGDY/CC). Our experiments and density functional theory (DFT) calculations show the 3D p-FGDY/CC network is highly active and it is ahigh potential metal-free catalyst for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), as well as overall water splitting (OWS) under both acidic and alkaline conditions.The experimental and theoretical resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…As shown in Figure 4D, the newly‐developed metal‐free COOH‐3.9‐MWNTs exhibited outstanding OER performance in acidic conditions, outperformed most noble metal (e.g., Ir‐ and Ru)‐based catalysts. To the best of our knowledge, they represent the best metal‐free electrocatalysts for the acidic OER 21–25,31–36 . The methodology developed in this work could also be applied for the design and development of new carbon catalysts for OER and many other reactions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Figure 4D, the newly‐developed metal‐free COOH‐3.9‐MWNTs exhibited outstanding OER performance in acidic conditions, outperformed most noble metal (e.g., Ir‐ and Ru)‐based catalysts. To the best of our knowledge, they represent the best metal‐free electrocatalysts for the acidic OER 21–25,31–36 . The methodology developed in this work could also be applied for the design and development of new carbon catalysts for OER and many other reactions.…”
Section: Resultsmentioning
confidence: 97%
“…Herein, we report a facile hydrothermal acid oxidation of CNTs to produce carboxyl‐enriched multiple‐walled carbon nanotubes (COOH‐MWNTs), which exhibited unprecedented OER performance in acidic conditions with a low overpotential of 265 mV at a current density of 10 mA cm –2 and a small Tafel slope of 82 mV dec –1 —better OER performance than that of any metal‐free electrocatalysts in acidic conditions reported to date 20–25 and comparable to those of the RuO 2 and IrO 2 benchmark catalysts. Our experimental observations combined with the theoretical calculations revealed a novel OER mechanism for the carboxyl‐enriched MWNTs catalysts, in which the carboxyl group lowers the energy barrier for water splitting via the formation and hydrolysis of a lactone.…”
Section: Introductionmentioning
confidence: 99%
“…The fluoro-GDY nanostructures on a carbon cloth (p-F-GDY/CC) network exhibited good performance as bifunctional catalysts for both HER and OER, as well as overall water splitting (OWS) under both acidic and alkaline conditions (Figure 7). 37 In the HER process, p-F-GDY/CC exhibited low onset overpotentials of 82 and 92 mV (versus the reversible hydrogen electrode) to achieve 10 mA cm −2 in both alkaline and acidic conditions, comparable to the metal-based catalysts. Extremely long stability over 8500 cycles in 1.0 M KOH verified the dramatic stability of F-GDY during the HER process.…”
Section: Heteroatom Dopingmentioning
confidence: 99%
“…(a) Schematic structure of F-GDY, (b) photograph of the p-F-GDY/CC material, (c) polarization curves of the catalysts for HER in 1.0 M KOH, (d) long-term stability tests of the p-F-GDY/CC in 1.0 M KOH during the HER process. Reproduced with permission from ref . Copyright 2019 Wiley-VCH.…”
Section: Application On Electrochemical Catalysismentioning
confidence: 99%
“…In the further study of GDY, it is found that due to the unique preparation process of GDY, the bottom-up synthesis method can be adopted for doping various heteroatoms into GDY qualitatively and quantitatively, which is conducive to improve the electrochemical behavior of GDY. To date, a variety of elements and groups have been successfully doped into GDY including H, Cl, F, N, CH 3 , NH, etc., and greatly changed the electrochemical performance of GDY. Both the heteroatoms substituting the carbon atoms in the benzene ring and the impurity groups replacing the acetylene chain make the morphological characteristics of GDY change from a combination of benzene rings and triangular apertures into a nanosheet consisting of benzene rings and hexagonal apertures.…”
Section: Introductionmentioning
confidence: 99%